Measuring food preference and reward: Application and cross-cultural adaptation of the Leeds Food Preference Questionnaire in human experimental research. (March 2020) - Oustric, Pauline; Thivel, David; Dalton, Michelle; Beaulieu, Kristine; Gibbons, Catherine; Hopkins, Mark; Blundell, John; Finlayson, Graham
Highlights: The LFPQ is a widely-used tool that measures liking and implicit wanting for food. Standards of good practice enable consistency in its adaptation and application. Appropriate food stimuli require both nutritional and perceptual validation. Validation of the task involves demonstration of its sensitivity and reliability. This protocol will improve comparability and quality of data generated by the LFPQ. Abstract: Decisions about what we eat play a central role in human appetite and energy balance. Measuring food reward and its underlying components of implicit motivation (wanting) and explicit sensory pleasure (liking) is therefore important in understanding which foods are preferred in a given context and at a given moment in time. Among the different methods used to measure food reward, the Leeds Food Preference Questionnaire (LFPQ) is a well-established tool that has been widely used in the scientific field for over 10 years. The original LFPQ measures explicit liking and implicit wanting for the same visual food stimuli varying along two nutritional dimensions: fat (high or low) and taste (sweet or savoury/non-sweet). With increasing use of the LFPQ (in original or adapted forms) across different cultural and scientific contexts, there is a need for a set of recommendations for effective execution as well as cultural and nutritional adaptations of the tool. This paper aims to describe the current status of the LFPQ for researchers new to the methodology, and to provide standards of good practice that can be adopted for its cultural adaptation and use in the laboratory or clinic. This paper details procedures for the creation and validation of appropriate food stimuli; implementation of the tool for sensitive measures of food reward; and interpretation of the main end-points of the LFPQ. Following these steps will facilitate comparisons of findings between studies and lead to a better understanding of the role of food reward in human eating behaviour.